Study on Hole Filling of Porous PU/PEG Membrane and its Mechanical Properties (Journal of Fiber Bioengineering and Informatics, 2010)
This study attempted to introduce porous technology into functional textile's formation, and developed a new way to improve working materials content in phase change material. Porous polyurethane (PU)/polyethylene glycol (PEG) membrane was prepared and selected as a supporting material. Considered to be convenient for filling, anhydrous ethanol was used to decrease PEG viscidity according to the rule of similarity. The solution of PEG and anhydrous ethanol were filled into porous PU/PEG membrane by vacuuming and then PU dry-film technology was used for the sealing of the membrane hole. The effects of PEG mass percentage in ethanol solution on filling rate and the filling rate on the membrane morphology and mechanical properties were studied. The results show that, the filling rate increased with the increase of PEG content in the blending solution. As the filling rate increased, the elongation at break decreased obviously, while the initial modulus increased largely. After sealing the filled membrane using PU dry-film technology, the initial modulus of the membrane decreased, while the elongation at break increased. In addition, DSC analysis indicates that the sealed membrane and pure PEG show similar thermal properties, while the compound membrane can retain its solid shape during phase change.
Keywords: Porous phase change membrane; polyurethane; polyethylene glycol; filling; mechanical properties